Green synthesis of the battery material lithium sulfide via metathetic reactions. Issue 36 (13th April 2022) - Fang, Liran; Zhang, Qiaran; Han, Aiguo; Zhao, Zixiang; Hu, Xiaohu; Wan, Fengming; Yang, Haoyu; Song, Dawei; Zhang, Xin; Yang, Yongan
Abstract : An innovative method that abides by all the standards of green chemistry for synthesizing high-purity lithium sulfide. Abstract : We report a synthesis of lithium sulfide, the cost-determining material for making sulphide solid electrolytes (SSEs), via spontaneous metathesis reactions between lithium salts (halides and nitrate) and sodium sulfide. This innovative method is economical, scalable and green. It will pave the way to developing practical SSE-based solid-state lithium batteries.